The Synthesis Of Quaternary Ammonium Salts With Carbonyl Functionality And Studies Of Their Physical Properties - Wong, Chan Hoong (2002)
This study is mainly focused on the synthesis of compounds of quaternary ammonium compounds. Iodoacetone has been produced through a simple method by reacting crystalline iodine and acetone in aqueous medium without adding any acid or base catalyst. Iodoacetone has been shown to react with various types of amines to produce tertiary and quarternary ammonium salts. For example, the reaction between pyridine and iodoacetone produced N-acetonyl pyridinium iodide. lodoacetone reacts with triethylamine to produce N-acetonyl triethylammonium iodide and it reacts with triethanolamine to produce N-acetonyl triethanolamonium iodide. The reaction has been shown to be a general one. In many cases, single crystal x-ray analysis was used to solve the structure of the salts. We have found that the crystal system for Nacetonyltrimethylammonium iodide, N-acetonyltriethylammonium iodide, Nacetonylpyridinium iodide, 1-( l -ethyl-2-oxo-propyl)-pyridinium iodide and 2-hydroxy-